Biomarkers of menopause - Jovičić, Snežana; Plebani, Mario (Archives of Pharmacy, 2025)
Natural menopause is defined as the permanent cessation of menstruation resulting from the loss of ovarian follicular activity. This significant phase in women’s reproductive aging has notable effects on fat distribution, dyslipidemia, and neurodegeneration. These changes contribute to an increased risk of dementia and cardiovascular disease as women age. Estimating the age at which natural menopause will occur is crucial for cancer survivors, women with a family history of premature ovarian insufficiency or early menopause, and those delaying their first pregnancy. Additionally, the timing of natural menopause is an important clinical indicator of longevity and a risk factor for morbidity and mortality. Beyond age and menstrual cycle characteristics, biomarkers related to menopause are essential for confirming its onset and predicting its premature occurrence.
Keywords: menopause; STRAW criteria; follicle stimulating hormone, FSH; inhibin B; anti-Müllerian hormone, AMH